School Choice to Lower Secondary Schools and Mechanisms of Segregation in Urban Finland - Kosunen Sonja; Bernelius Venla; Seppänen Piia; Porkka Miina (Sage Publications, 2022)
We explore the interconnections of pupil admission and school choice with the socioeconomic composition of schools in the city of Espoo, Finland. We analyze pupil enrollment from residential areas, and compare the schools’ expected and actual socioeconomic profiles using GIS software (MapInfo). Social-diversification mechanisms within urban comprehensive schooling emerged: Distinctive choices of language and selective classes are made predominantly by pupils from residential blocks with higher socioeconomic profiles. The role of urban segregation in school choice seems to be stronger than predicted. As mechanisms of educational distinction accompanied with grouping policies, choice leads to socioeconomic segregation across and within schools.